The Interest to Buy Home Industry Products of the Baduy Tribe: the Effectiveness of Sharia Marketing Mix and Religiosity - Najmudin Najmudin; Syihabudin Syihabudin; Ma'zumi Ma'zumi; Sujai Sujai; Nanah Sujanah (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
This study aims to analyze (1) the effect of sharia marketing mix on the interest in buying Baduy ethnic home industry products, (2) the influence of religiosity on the interest in buying the Baduy ethnic home industry products, and (3) the influence of the sharia marketing mix and religiosity on the interest in buying home industry products. Baduy tribe. The object of this research is the home industry product of the Baduy Tribe. Respondents who became the research population were visitors to the Baduy Tribe settlement and prioritized consumers who had bought Baduy Tribe home industry products. The sample taken in this study amounted to 85 respondents. The research method used is a quantitative method with data collection methods in the form of a questionnaire. Data were analyzed using a multiple linear regression test. The results of this study indicate that (1) the Islamic marketing mix has a significant positive effect on the interest in buying Baduy ethnic home industry products, (2) religiosity has a significant positive effect on the interest in buying Baduy home industry products. (3) Islamic marketing mix and religiosity have a significant positive effect on the interest in buying Baduy ethnic home industry products, with a total contribution 29.8 percent influence, while the remaining 70.02 are influenced by other variables not examined in this research.